Evaluating The Impact of E-Learning on Girl’s Education in Afghanistan: A Case study of Samangan University - Hakimi, Musawer; Fazil, Abdul Wajid; Khaliqyar, Khudai Qul; Quchi, Mohammad Mustafa; Sajid, Saidamin (International Journal of Multidisciplinary Approach Research and Science, 2024)
This study delves into the impact of E-Learning on girls' education at Samangan University in Afghanistan, focusing on evaluating the efficacy of digital programs within the nation's intricate socio-cultural landscape. The research, encompassing responses from 106 female students through surveys, highlights the critical need for robust infrastructure, reliable internet access, and accessible devices to facilitate active participation in digital learning. Teacher training programs emerge as pivotal for the successful implementation of E-Learning. Factors such as learning support systems and the overall learning experience play significant roles in shaping student engagement and satisfaction. Despite these positive aspects, social barriers, notably gender discrimination, persist, impeding female students' access to and engagement in digital learning. In conclusion, the study suggests that E-Learning holds immense potential to broaden educational opportunities in Afghanistan. It emphasizes the necessity of substantial infrastructure investment, comprehensive teacher training, and addressing social inequalities to foster an inclusive learning environment. Policymakers and educational institutions can leverage these insights to formulate strategies ensuring equitable access to quality education for all female students at Samangan University. The research significantly contributes valuable guidance for prospective investigations and the development of E-Learning initiatives, emphasizing the transformative role of digital learning in advancing education in Afghanistan, particularly for female students.